Medium altitude training and sea-level performance - Telford, R. D.; Graham, K. S.; Sutton, J. R.; Hahn, A. G.; Campbell, D. A.; Creighton, S. W.; Cunningham, R. B.; Davis, P. G.; Gore, C. J.; Smith, J. A. (Medicine & Science in Sports & Exercise, 1996)
Medium altitude training is widely used with a view to improving sea-level performance. Elite male distance runners (N = 18) were divided into groups matched for previous and planned training as well as several aerobic parameters. The altitude training group lived and trained at 1700-2000 m. It was concluded that after four weeks at medium altitude no advantage over sea-level training improved 3.2 Km running performance in already well-trained elite runners. Implication: This study was carefully controlled and involved very elite athletes. No benefit from moderate-altitude training was revealed.